State of the object and state’s indicators. Problems of personnel management - M. S. Mokiy; M. E. Cortés (Управление)
The article substantiates the thesis that in personnel management it is necessary to distinguish between the object state and the object state indicators. The study of employee behavior from the standpoint of a system-transdisciplinary approach allowed us to conclude that any employee strives for stability and self-preservation. The condition for maintaining the stability and development of the employee is to achieve the indicators that the manager gives him. However, this doesn’t always change the object state. The main problem of personnel management is the development of a set of indicators, in which, working on indicators, employees would change the state of the organization in the right direction. The interpretation of economic relations as a system allows us to designate their basic element as a household. Then the objective function of economic relations is to meet the needs of all households. It is shown that the existing system of monetary indicators at the state level cannot provide an increase in the well-being of all households. The necessity of developing evaluation indicators of the activities of decision-makers and managers based on the designated system goal of the development of the national economy is justified. The problems of developing indicators and ways to solve them are also outlined.